UPAYA PENINGKATAN KETERAMPILAN GURU DALAM MENULIS INSTRUMEN PENILAIAN DENGAN TEKNIK TIRU MODEL MELALUI SUPERVISI ASSESSMENT - Nisdawati Nisdawati (STKIP Rokania Pasir Pangaraian, 2019)
This research aims to find information about teacher's skill level in writing assessment instrument with modeling technique through assessment supervision on teacher of SD Negeri 006 Rambah. The research method used is a descriptive method which is done in two cycles. Each cycle consists of four stages of research, namely planning, implementation, observation, and reflection. This research data is the result of assessment supervision on teachers in writing assessment instruments, field notes and results of teacher writing skill. The result of activity data and field note writing assessments were analyzed qualitatively. The result data of the scoring writing skill is analyzed quantitatively. The results showed that the modeling technique that is used as a research technique can improve the teacher's skill in writing the assessment instrument. Through modeling techniques, clever teachers can guide other teachers that need it. Teachers are motivated to learn and try to achieve further success. Based on the category of capability that has been established in this research, it turns out for each cycle of the results of the ability of teachers always increase, so that the research is achieved, i.e. teachers who achieve the ability≥76% of the number of teachers. From these results, it can be concluded that the modeling techniques can improve the writing skills of teacher assessment